Selective distribution of kainate receptor subunit immunoreactivity in monkey neocortex revealed by a monoclonal antibody that recognizes glutamate receptor subunits GluR5/6/7 - Huntley, GW (J Neurosci, 1993)
A monoclonal antibody (4F5) was generated against a portion of the putative extracellular domain of glutamate receptor subunit GluR5. Western blot analyses and immunocytochemistry of transfected human embryonic kidney 293 cells confirmed that monoclonal antibody 4F5 was specific for GluR5, -6, and -7 (the three identified members of the kainate receptor subunit class), but did not recognize GluR1, -2, or -3 (the AMPA/kainate receptor subunit class). The antibody was subsequently used to examine immunocytochemically the regional, laminar, and cellular distribution of GluR5/6/7 receptor subunits at the light and electron microscopic levels in monkey neocortex. Receptor subunit immunoreactivity was present throughout all cortical areas examined, but exhibited marked cellular, laminar, and regional specificity. Typically, pyramidal cell somata and apical dendrites were well stained. Electron microscopy revealed an extensive cytoplasmic localization of GluR5/6/7 immunoprecipitate, with intense staining of many postsynaptic densities, all of which were associated with asymmetric synapses located on dendritic shafts or dendritic spines. There was no evidence of stained glial cells or presynaptic axon terminals. In most areas, labeled cells and dendrites were concentrated in layers II, III, and V while layers I, IV, and VI typically possessed the fewest and/or least intensely stained elements. A consistent feature in many areas was groups of clustered layer V pyramidal cells and bundles of ascending apical dendrites. Regionally, motor areas and higher-order association areas of the frontal, parietal, and occipital lobes were more densely stained than primary sensory areas (somatic sensory and visual cortex), which was confirmed quantitatively. These data indicate a high degree of selectivity in the distribution of kainate receptors composed of GluR5/6/7 subunits, and suggest that functional specificity and diversity in the ubiquitous excitatory amino acid-utilizing axonal systems in neocortex are achieved in part by the differential association of particular glutamate receptor subunits with specific cortical circuits. In addition, the regional, laminar, and morphological characteristics of GluR5/6/7-immunoreactive neurons bear a strong similarity to those of the neocortical neurons with heightened vulnerability in certain neurodegenerative disorders.